The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1063/1.5023830
|View full text |Cite
|
Sign up to set email alerts
|

Designing superhard metals: The case of low borides

Abstract: The search for new superhard materials has usually focused on strong covalent solids. It is, however, a huge challenge to design superhard metals because of the low resistance of metallic bonds against the formation and movement of dislocations. Here, we report a microscopic mechanism of enhancing hardness by identifying highly stable thermodynamic phases and strengthening weak slip planes. Using the well-known transition-metal borides as prototypes, we demonstrate that several low borides possess unexpectedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Consequently, the calculated bulk modulus of TiC from first-principles calculation is only 252.4 GPa, which is far lower than that of diamond, Os, and the osmium di-borides. However, according to recent reports of S. H. Jhi and Y. C. Liang, a valence electron number of eight will result in the most reasonable electronic structure, and thus higher hardness [31][32][33][34]. The valence electron of TiC is about eight electrons, and this may be one of the reasons for its exceptionally high hardness.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the calculated bulk modulus of TiC from first-principles calculation is only 252.4 GPa, which is far lower than that of diamond, Os, and the osmium di-borides. However, according to recent reports of S. H. Jhi and Y. C. Liang, a valence electron number of eight will result in the most reasonable electronic structure, and thus higher hardness [31][32][33][34]. The valence electron of TiC is about eight electrons, and this may be one of the reasons for its exceptionally high hardness.…”
Section: Resultsmentioning
confidence: 99%
“…Superhard materials have long attracted tremendous attention for a wide range of applications, such as high-temperature applications, surface protection, and abrasive materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Diamond is the hardest substance, which maintains records of bulk modulus, shear modulus, and high hardness of 432 GPa, 535 GPa, and 60-150 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The balance of high hardness and excellent metallicity is a central challenge to design superhard metals. However, great success has been achieved with the discovery of transition-metal (TM) light-element (LE) compounds [7][8][9][10][11][12][13][14][15]. It is generally believed that their high hardness stems from a combination of high valence-electron concentration to resist volume compression and strong covalent bonding to counteract shape deformation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Superhard metals show excellent performance, including the high hardness, wear resistance, good thermodynamic stability and metallic behavior, compared with traditional superhard materials. [ 1–9 ] The superhard metals can be synthesized by inserting strong covalent bonds of light element (LE), such as carbon, boron, nitrogen, into transition metal (TM) with a large number of valence electrons. Based on the classical thought, to obtain a high hardness, a straightforward way was to incorporate more light atoms into the transition metal to form strong covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Liang et al also found that several low borides showed unexpectedly high hardness, while the hardness reduced for high borides. [ 2 ] Lu et al predicted the hardness of hP4‐WN and hP6‐WN 2 exceeded 40 GPa using the first principles. [ 12 ] The high hardness and low light element content in TM‐LE compound makes the superhard metal possible.…”
Section: Introductionmentioning
confidence: 99%